The role of structural empowerment in promoting proactive behavior: An analytical study of the opinions of a sample of employees of the Karbala Holy Municipality Directorate. - Muhammad Mohsen, Ali; Younes, Arivan; hatef Abid Al-Sada, Meethaq (Iraqi Journal for Administrative Sciences, 2024)
This research seeks to determine the effect of structural empowerment on proactive behavior. Through its dimensions (prevention of problems, voice of work, responsibility and creativity of work), the research problem started from the reality of the Karbala Municipality Directorate, which did not achieve the required level in providing its services to its beneficiaries. Although its administration is trying hard to enhance the proactive behavior of its personnel in order to reach the highest levels between local and regional organizations, a hypothetical scheme has been built that reflects the researcher’s perceptions of the nature of the relationship between the variables and how the situation of the Holy Karbala municipality can change, according to two main hypotheses, the first relating to The content of the correlation relationship (there is a statistically significant correlation between structural empowerment and proactive behavior), while the second hypothesis concerns the level of influence between the two variables with its content (there is a significant effect relationship between structural empowerment and proactive behavior in its dimensions at the level of the Holy Karbala Municipality Directorate).The research was conducted in the Directorate of Karbala Municipality (the center), as the necessary information for the field side was obtained through the questionnaire prepared for this purpose. The practical side, including (Cronbach’s alpha coefficient, arithmetic mean, standard deviation, Pearson correlation coefficient, simple regression analysis, (F) test, coefficient of determination (R2), and marginal slope coefficient (β). Through programs Statistics (SPSS.V.25). The research reached several results, including the presence of a statistically significant effect between structural empowerment and proactive behavior, and based on the results, the researcher presented a set of recommendations, the most prominent of which is that the Karbala Municipality Directorate seeks to increase interest in the side of structural empowerment of its employees for the purpose of achieving its planned goals, and seeking to increase interest In addition to the proactive behavior of its employees in order to arouse their talents and intellectual abilities to enable them to develop appropriate solutions to work problems that may hinder the completion of their tasks.